Physician associate preceptorship: Experience of a novel programme in Inverness - Liam Allan; Duncan Scott; Ed Paterson; Tony Golabek (Future Healthcare Journal)
Physician associates (PAs) are a developing profession in the UK. The Faculty of Physician Associates (FPA) recommends the establishment of local preceptorship programmes for PAs in the first year of practice who have successfully passed the PA national exam. Limited evidence currently exists around the evaluation of such local programmes and the experience of the intern PAs involved.Over the course of a 12-month period, four intern PAs completed a structured preceptorship comprising clinical supervision, teaching and mentoring. Upon completion of this programme, qualitative data were recorded and analysed to influence the development of the preceptorship in future.In conclusion, a structured preceptorship has been shown to be a useful method of improving clinician confidence and competence while offering a supported working environment for newly qualified PAs.